The Effectiveness of Multimedia-Based Learning To Accelerate Learning After The Pandemic At The Basic Education Level - Tuhuteru, Laros; Misnawati, Desy; Aslan, Aslan; Taufiqoh , Zakiyatut; Imelda , Imelda (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This study discusses multimedia's effectiveness for accelerated or post-pandemic low learning at the elementary school level. Very few data findings discuss the effectiveness of post-pandemic technology-based learning. An electronic data search will be carried out on various literature related to the two variables above to overcome this problem. Next, we analyze the data using a phenomenological approach that involves a deep data coding system and high integration and ends with the principle of high validity to answer the issues and problems we have formed above. After going through a series of studies and presentation of existing data, this study is believed to have produced several findings, including the application of multimedia for the elementary level, efforts to accelerate learning loss due to the impact of the Pandemic have proven to be able to provide several conveniences and be innovative in its implementation. The reason is that multimedia attracts learners and allows learning to find new things that cannot be done manually. These findings will be the best contribution to the development of multimedia learning for post-pandemic elementary schools.